2014
DOI: 10.1111/ejh.12262
|View full text |Cite
|
Sign up to set email alerts
|

An overview of platelet indices and methods for evaluating platelet function in thrombocytopenic patients

Abstract: Thrombocytopenia is associated with bleeding risk. However, in thrombocytopenic patients, platelet count does not correlate with bleeding risk and other factors are thus likely to contribute to this risk. This review presents currently available platelet-related markers available on automated haematology analysers and commonly used methods for testing platelet function. The test principles, advantages and disadvantages of each test are described. We also evaluate the current literature regarding the clinical u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 79 publications
(153 reference statements)
0
57
1
12
Order By: Relevance
“…In our study we did not find an inverse correlation between MPV values and platelet count that Lance et al found [23]. The other platelet volume indices, PDW and P-LCR have been less studied in comparison to MPV [11,24]. In our study MPV and the others PVI, assessed through the impedance method, did not reveal a significant difference between values of patients and healthy controls.…”
Section: Discussioncontrasting
confidence: 70%
“…In our study we did not find an inverse correlation between MPV values and platelet count that Lance et al found [23]. The other platelet volume indices, PDW and P-LCR have been less studied in comparison to MPV [11,24]. In our study MPV and the others PVI, assessed through the impedance method, did not reveal a significant difference between values of patients and healthy controls.…”
Section: Discussioncontrasting
confidence: 70%
“…Research has shown that reduced myeloproliferative function leads to a decrease in PLT, while MPV is reduced or remains unchanged (Chandra et al, 2010). Vinholt et al (2014) suggested that the bleeding symptoms in thrombocytopenia patients may be related to a decrease in MPV. The results of this study indicated that childhood ALL incorporates thrombocytopenia and platelet dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of reduction in the number of platelets is a determinant to assess the risk of bleeding. Patients with a low platelet count diagnosed and treated for a long period of time presented a very small amount of bleeding; however, patients with high platelet counts faced serious bleeding; therefore, bleeding was said to be associated with platelet function (Vinholt et al, 2014). Platelets have a short life span, and are not easily preserved; this hinders the clinical detection of platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…It remains the gold standard method for assessing platelet reactivity in both clinical and research settings. However, abnormal platelet aggregation studies (demonstrating hypofunction or hyperfunction) often lack correlation with clinical complications (bleeding or thrombosis) [14,15] . This method is useful for detecting platelet function defects that are congenital or secondary to medication.…”
Section: Platelet Function Assaymentioning
confidence: 99%